Effects of POE and Carbon Black on the PTC Performance and Flexibility of High-Density Polyethylene Composites - Feng Xue; Kangcai Li; Lei Cai; Enyong Ding (Advances in Polymer Technology)
High-density polyethylene (HDPE)/carbon black (CB) is widely used in positive temperature coefficient (PTC) composites. In order to expand its applications to fields that need good flexibility, polyolefin elastomer (POE) was incorporated into HDPE/CB composites as a secondary thermoplastic elastomer phase to provide flexibility. The effects of POE and CB content on the PTC performance and flexibility were investigated. Micro morphology and crystallization behavior are closely related to PTC properties. SEM was conducted to reveal phase morphology and filler dispersion, and DSC was conducted to research crystallization behavior. The results show that the incorporation of 18 wt.% POE can decrease the percolation threshold of conductive carbon black from 22.5 wt.% to 16 wt.%. When the CB content is 30 wt.%, the room temperature resistivity gradually increases with the increasing content of POE because of the barrier effect of POE phase, and the PTC intensity is gradually enhanced. Meanwhile, the PTC switching temperature shifts down to a lower temperature. The incorporation of 18 wt.% POE significantly increases the elongation at break, reaching an ultrahigh value of 980 wt.%, which means great flexibility has been achieved in HDPE/POE/CB composites. This work provides a new method of fabricating PTC composites with balanced electrical and mechanical properties.